Deep Moral Disagreement and Unthinkable Possibilities - Caprioglio Panizza, Silvia (Taylor & Francis, 2025)
Some disagreements seem to find no resolution, despite exchange of argu-ments and lack of obvious epistemic vices. These ‘deep disagreements’ havepuzzled philosophers, who have offered different epistemological explanationsfor their ‘depth’. Deep disagreements that are moral in nature are more rarelydiscussed. What explains the ‘depth’ in the moral cases? This paper proposesthat most deep moral disagreements can be explained by appealing tomutually unthinkable practical possibilities. Specifically, deep moral disagree-ments are those where each party demands the actualisation of a possibilitythat is unthinkable to the other party, and what determines the unthinkability isthe structural role of value as ‘hinge commitment’, functioning both as back-ground and as excluder. Using as example the debate on abortion, recentlyreignited in the US by the overturning of Roe v. Wade, the paper aims to offera model to understand deep moral disagreements, where value functions not(only) as topic but as structure.
Keywords: deep disagreement; deep moral disagreement; hinge commitments; practical possibilities; unthinkability; abortion debate